The awareness of BBA student in UiTM Malacca City Campus towards unit trust investment with Amanah Saham Nasional Berhad: a research study of Amanah Saham Nasional Berhad (ASNB) / Nur Muhammad Mohammmad Noh - Mohammmad Noh, Nur Muhammad (Faculty of Business and Management, 2012)
Every single company needs strategies in order to survive or to become a leader in the market nowadays, therefore a study towards findings the suitable strategies for Amanah Saham Nasional Berhad had been carried out. The purpose of the study is to identify the awareness of BBA student from UiTM Malacca City Campus towards unit trust investment, to identify the factors contribute to the awareness towards unit trust investment and to examine the most effective factor contribute to the awareness. A good research design will ensure that the marketing research project is conducted effectively. In this research, the exploratory research, descriptive and causal effect has been used. The target sampling size for this study is 100 respondents where the questionnaires were distributed to BBA students in UiTM Malacca City Campus. For this study, the non-probability sampling technique has been chosen. The non-probability sampling method will be used is convenience sampling. Moreover, computer programs have been developed to simplify and ease the research tabulation and analysis task. One of the most accurate and dependable statistical analysis packages is Statistical Package for Social Science (SPSS). The researcher used primary and secondary data in order to gather data. The findings are being interpreted using correlation coefficient in order to test the hypothesis. This research also uses descriptive statistics in order to find out the most factors that contribute towards awareness in unit trust investment. Base on the finding, attribute advertising, personal selling, public relation and sales promotion have positive relationship with the awareness. Besides, it also shows that public relation is the most preferable factors that contribute towards awareness in unit trust investment